A Randomized Controlled Trial on the Effect of Tapentadol and Morphine on Conditioned Pain Modulation in Healthy Volunteers. - Chris Martini; Monique van Velzen; Asbjørn Drewes; Leon Aarts; Albert Dahan; Marieke Niesters (PLoS ONE)
Background Modulatory descending pathways, originating at supraspinal sites that converge at dorsal horn neurons, influence pain perception in humans. Defects in descending pain control are linked to chronic pain states and its restoration may be a valuable analgesic tool. Conditioned pain modulation (CPM) is a surrogate marker of descending inhibition that reduces the perception of pain from a primary test stimulus during application of a conditioning stimulus. Here the effects of the analgesics tapentadol, a combined mu-opioid receptor agonist and noradrenaline reuptake inhibitor, and morphine, a strong mu-opioid receptor agonist, were tested on CPM in a randomized, double-blind, placebo-controlled crossover trial in 12 healthy pain-free volunteers, to understand possible differences in mechanism of action between these opioids. Methods and results On three occasions CPM responses were obtained 60-90 and 120-150 min following intake of tapentadol (100 mg immediate release tablet), morphine (40 mg immediate release tablet) or placebo. At both time points, CPM was detectable after treatment with placebo and tapentadol (peak pain ratings reduced by 20-30% after application of the conditioning stimulus) but not after morphine. Compared to placebo morphine displayed significantly less CPM: mean treatment difference 18.2% (95% CI 3.4 to 32.9%) at 60-90 min after drug intake and 19.5% (95% CI 5.7 to 33.2%) at 120-150 min after drug intake (p = 0.001). No difference in CPM between placebo and tapentadol was detected: mean treatment difference 1.5% (95% CI -11.6 to 14.6%) at 60-90 min after drug intake and 1.5% (95% CI -16.0 to 18.9%) at 120-150 min after drug intake (p = 0.60). Conclusions Our data show that in volunteers morphine affects CPM, while tapentadol was without effect despite identical experimental conditions. These data confirm that tapentadol's main mechanism of action is distinct from that of morphine and likely related to the effect of adrenergic stimulation on descending controls. Trial registration Netherlands Trial Register NTR2716.